Studies on pine ectendomycorrhizae in nurseries - Roman Pachlewski; Jadwiga Kermen; Elżbieta Chruściak; Maria Trzcińska (Acta Mycologica, 2014)
Fungus isolates from ectendomycorrhizae of Pinus sylvestris seedlings showed uniform morphological, physiological and mycorrhizal features. Studies on hyphal ultrastucture suggest that the fungus is an Ascomyceles. Growth of cultures in vitro and formation of ectendoroycorrhizae in the nursery were stimulated both by Ca compounds and urea. Strains of the fungus showed considerable ability to synthesize nitrate reductase. The Studies provided evidence of a permanent occurrence of N2-fixing Bacillus polymyxa in the ectendomycorrhizosphere.